Correlation between performance in repeated sprints and performance in other laboratory and field fitness tests in female soccer athletes - Kotsakis, P.; Michailidis, Y.; Svynos, G.; Mandroukas, A.; Gissis, I.; Metaxas, T. (Trends in Sport Sciences, 2023)
Introduction. The ability to perform repeated sprints is one of the most important physical abilities in soccer. Aim of Study. The aim of this study was to examine the relationship between the ability to perform repeated sprints (6 × 20 m in a 15-s cycle) in female soccer players from two different age groups, with aerobic capacity (YYIR1), jumping ability (single-leg hop test), isokinetic strength (60°/s, 180°/s, 300°/s), speed performance (S10-m and S30-m), and change of direction ability (505 COD test). The second objective of the study was to compare the performances of the two different groups in the tests. Material and Methods. Twenty-four female soccer players from Greece participated in this study and they were divided into two groups: (i) U-16 (division II) female soccer athletes (age: 15.8 ± 0.8 years, height: 160.5 ± 5.1 cm, body mass: 59.4 ± 7 kg), and (ii) adult female (division I) soccer athletes (age: 21.9 ± 4.1 years, height: 165.7 ± 6.1 cm, body mass: 62.2 ± 7.5 kg). The Pearson correlation coefficient and t-test for independent samples were used for statistical analysis. Results. The S10-m, S30-m and single-leg hop tests appeared to be the variables most associated with the total time in the RSA test in U-16 female soccer players. S10-m and the change of direction ability appeared to be the variables most associated with the total time in the RSA test in adult female players. Conclusions. It seems that U-16 Greek female soccer players do not differ from adults in most of the physical fitness tests conducted in the field and laboratory.